2019
DOI: 10.1016/j.chom.2019.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Redondoviridae, a Family of Small, Circular DNA Viruses of the Human Oro-Respiratory Tract Associated with Periodontitis and Critical Illness

Abstract: Highlights d A family of human DNA viruses was identified and named Redondoviridae d Redondoviruses were the second most common virus in human respiratory virome samples d Some subjects with periodontitis and critical illness had higher redondovirus levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 90 publications
4
99
1
Order By: Relevance
“…Both had the typical structure of the CRESS-DNA viruses, with two open reading frames (ORF), one encoding a helicase (Rep) and one encoding the capsid protein (Cap). A third ORF overlapping the capsid gene was detected that codes for a leucine-rich protein (34% Leu + Ile), similar to the ORF3 of the recently described Redondoviridae [12]. The two genomes had a small intergenic region of 178 and 175 nucleotides between the 5' end of the Cap and Rep genes, with a potential stem loop sequence and a large intergenic region of 239 and 238 nucleotides between the 3' ends of the two genes.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Both had the typical structure of the CRESS-DNA viruses, with two open reading frames (ORF), one encoding a helicase (Rep) and one encoding the capsid protein (Cap). A third ORF overlapping the capsid gene was detected that codes for a leucine-rich protein (34% Leu + Ile), similar to the ORF3 of the recently described Redondoviridae [12]. The two genomes had a small intergenic region of 178 and 175 nucleotides between the 5' end of the Cap and Rep genes, with a potential stem loop sequence and a large intergenic region of 239 and 238 nucleotides between the 3' ends of the two genes.…”
Section: Resultsmentioning
confidence: 65%
“…The capsid and ORF3 genes of the two variants were almost identical (about 99% protein sequence identity), while their helicase genes were considerably divergent (53.4% protein sequence identity), explaining why there was twice the coverage of the initial mapping against this sequence for the Cap region as compared to the Rep region. Phylogenetic relationship to other known CRESS-DNA viruses, including the closely related human respiratory circovirus-like viruses (Genbank accession numbers KJ433989, KY214434, KY052047, KY349925, and KY244146) and members of the genus Redondoviridae [12], were studied using the whole-genome nucleotide sequences, and the Cap and Rep protein sequences. Maximum-likelihood phylogenetic analysis with the Rep protein sequences (since the Cap protein sequences had about 99% protein sequence identity) showed that the two HRCLVs were located within the vientoviruses branch ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although recent metagenomic studies have resulted in the discovery of many novel ssDNA viruses, issues such as reagent contamination and low protein/nucleotide similarity has complicated analysis and classification [18,19,32]. Currently, the ICTV recognises 11 families of ssDNA viruses, with several new families discovered recently including the Genomoviridae, Redondoviridae, and Smacoviridae [13,15,33]. Known invertebrate ssDNA viruses include members of the Parvoviridae, Circoviridae, and Bidnaviridae, and recent metagenomic studies have recently identified ssDNA in a variety of invertebrates, including termites [34], pine beetles [35] honey bees [36], dragonflies [6], and a range of marine and terrestrial invertebrates [9,37].…”
Section: Discussionmentioning
confidence: 99%
“…Known invertebrate ssDNA viruses include members of the Parvoviridae, Circoviridae, and Bidnaviridae, and recent metagenomic studies have recently identified ssDNA in a variety of invertebrates, including termites [34], pine beetles [35] honey bees [36], dragonflies [6], and a range of marine and terrestrial invertebrates [9,37]. Similarly, CRESS DNA viruses, that contain many ssDNA virus families (including the Genomoviridae, Smacoviridae, Bacilladnaviridae, and Circoviridae), have also been sampled from invertebrates [33], as well as from such diverse environments as oceans and estuaries [38,39] and even poxvirus lesions in tanagers [31]. We add to this diversity by identifying novel species and variants of previously identified species of ssDNA viruses from the Circoviridae, Genomoviridae, and Parvoviridae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation